2018
DOI: 10.1097/qai.0000000000001711
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Systemic Inflammation, Immune Activation, and Impaired Lung Function Among People Living With HIV in Rural Uganda

Abstract: Macrophage activation and systemic inflammation are associated with lower lung function among PLWH on stable ART in rural Uganda. Future work should focus on underlying mechanisms and public health implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 49 publications
(48 reference statements)
0
21
0
Order By: Relevance
“…Based upon similarities in their relationships with systemic inflammation [7, 60] and lung disease [57, 6264], chronic HIV infection and air pollution may act synergistically to worsen respiratory morbidity among co-exposed populations. Indeed, we previously found that systemic inflammation varied according to both biomass use and HIV serostatus in this cohort, and that higher indices of systemic inflammation were associated with worse lung function among both PLWH and HIV-uninfected controls [65]. Alternatively, air pollution exposure may increase the risk of pulmonary tuberculosis through smoke-induced endothelial and alveolar damage that facilitates mycobacterial infection [8, 66] and/or altered antimycobacterial innate immunity [67].…”
Section: Discussionmentioning
confidence: 99%
“…Based upon similarities in their relationships with systemic inflammation [7, 60] and lung disease [57, 6264], chronic HIV infection and air pollution may act synergistically to worsen respiratory morbidity among co-exposed populations. Indeed, we previously found that systemic inflammation varied according to both biomass use and HIV serostatus in this cohort, and that higher indices of systemic inflammation were associated with worse lung function among both PLWH and HIV-uninfected controls [65]. Alternatively, air pollution exposure may increase the risk of pulmonary tuberculosis through smoke-induced endothelial and alveolar damage that facilitates mycobacterial infection [8, 66] and/or altered antimycobacterial innate immunity [67].…”
Section: Discussionmentioning
confidence: 99%
“…In several of the included studies, sample size or power calculations are not included, limiting the external validity of their findings. Four of the included studies were at risk of observer bias due to the lack of reported blinding of the investigators, radiologists or interpreters [36,3840]. In addition, several studies are at risk of sampling bias [35,36,40].…”
Section: Resultsmentioning
confidence: 99%
“…Four of the included studies were at risk of observer bias due to the lack of reported blinding of the investigators, radiologists or interpreters [36,3840]. In addition, several studies are at risk of sampling bias [35,36,40]. In North et al , groups were chosen by convenience sampling [40], while in Attia and Triplette [35,37], patients were chosen from a veteran population, which limits the generalizability of these results [35,37].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also known to cause many extra-hepatic manifestations including auto-immune thyroid disease 16. Impaired lung functions have also been demonstrated in HIV infection and fatty liver disease 17,18. HCV produces many inflammatory mediators including TNF-α, TGF-β, interleukin (IL-6), and IL-8 by altering cellular signalling and genetic imbalances 19.…”
Section: Discussionmentioning
confidence: 99%